Regenerated chitin reinforced polyhydroxybutyrate composites via Pickering emulsion template with improved rheological, thermal, and mechanical properties. (June 2021) - Baraki, Senay Yacob; Zhang, Yunchong; Li, Xiang; Ding, Lei; Debeli, Dereje Kebebew; Macharia, Daniel K.; Wang, Bija; Feng, Xueling; Mao, Zhiping; Sui, Xiaofeng
Abstract: Nanochitin is a promising nanofiller for the development of nanocomposites materials, whose overall performance is greatly dependent on the dispersity of the filler. Here, we employed the Pickering emulsion platform to prepare a uniformly distributed regenerated nanochitin (RCh)/polyhdroxybutyrate (PHB) composites. The produced PHB/RCh nanocomposites were studied for their thermal, mechanical, and rheological properties. It was found that the addition of 1.5% RCh markedly increased the thermal decomposition temperature by 24 °C than pure PHB. Similarly, both the storage modulus and tensile strength were also improved by 37% and 45%, respectively with regards to the neat PHB. Moreover, the rheological results also elucidated that the introduction of RCh improved the viscoelastic characteristics of the neat PHB over the frequencies range. Thus, the Pickering emulsion technique provides a simple and green method for preparing RCh-reinforced polymer nanocomposite materials used in packaging applications. Graphical abstract: Image 1 Highlights: RCh-reinforced PHB composites were prepared by a simple Pickering emulsion method. Storage modulus and tensile strength were enhanced by 37% and 45%, respectively. The addition of RCh improved composite initial decomposition temperature by 24 °C.